Successful management of an Rh alloimmunised twin gestation pregnancy with multiple atypical antibodies with severe fetal anemia - Sikarwar, Rakhi; Satia, Meena; Panchbudhe, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Rhesus-D alloimmunization is characterized by production of antibodies as a result of immune response generated in an individual due to exposure to alloantibodies from different individual. Here we are reporting a case of successful obstetric and perinatal outcome of twin pregnancy with Rh-incompatibility along with other atypical antibodies leading to fetal and neonatal anemia in both the twins. Antenatal management consisted of serial obstetric Doppler to look for Middle cerebral artery blood flow and Peak systolic velocity to detect fetal anemia followed by Intra Uterine transfusion of packed red cells through umbilical vein to treat the same for both the twins. In the presence of multiple atypical antibodies in the maternal serum no compatible blood was available for transfusion for either the mother or the neonates after delivery so NICU management consisted initially of transfusion of intravenous immunoglobulin’s along with steroids to prevent auto and alloantibody reactions but in view of dropping hemoglobin in both twins least incompatible blood was given to both the twins.